Factors Affecting Employee Performance At Bank Syariah Indonesia KCP Balikpapan Baru - Nuratfal Romadhan Asmi; Norvadewi; Yovanda Noni (International Journal of Management and Business Economics, 2023)
The background of this research is competition in providing services in the Islamic banking industry, which has led to a large increase in public trust. Therefore, companies must have competent human resources and be able to compete with other companies because human resources are the most important element in the success and continuity of operational activities in a company. This study uses quantitative research. With the population used, namely all employees of Islamic banks at PT. Bank Syariah Indonesia KCP Balikpapan Baru, and the samples used, there were 20 respondents with saturated sampling technique.  The results of this study are, partially, leadership style with a value of (THitung > TTabel) 2.891 > 2.14479, work environment with a value of 2.865> 2.14479, and motivation with a value of 19.558 >2.14479, so that they influence and are significant on the performance of employees of PT. Bank Syariah Indonesia, KCP Balikpapan Baru. Then the work ethic has a value of (THitung < TTabel) 1.332 < 2.14479, so it does not have a significant influence on the performance of employees of PT. Bank Syariah Indonesia New Balikpapan KCP. Then simultaneously, leadership style, work ethic, work environment, and motivation equally affect the performance of employees of PT. Bank Syariah Indonesia, KCP Balikpapan Baru, with a value of 103.263 > 3.06 and has an R2 contribution value of 96.8%.